The Philosophy of Islamic Education Policy: An Ontological, Epistemological, and Axiological Analysis of Islamic Religious Education Policy - Rahmat Zubandi Thahir; Abd. Muis (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
This study aims to analyze the philosophical foundations of Islamic Religious Education (IRE) policy through the integrated perspectives of ontology, epistemology, and axiology using a qualitative literature review approach. Data were collected from peer-reviewed journal articles, scholarly books, conference proceedings, and institutional reports related to Islamic educational philosophy and educational policy. The literature was analyzed using thematic analysis to identify conceptual patterns, theoretical relationships, and emerging perspectives. The findings indicate that ontology explains the nature and purpose of Islamic education based on the principles of tawhid and holistic human development; epistemology emphasizes the integration of revelation, reason, empirical inquiry, and critical reflection in educational policymaking; while axiology highlights Islamic ethical values as the normative foundation for educational objectives, curriculum development, and institutional governance. This study contributes to the development of Islamic education policy theory by proposing an integrated philosophical framework that bridges fragmented philosophical discussions and provides practical guidance for designing value-based, philosophically coherent, and contextually relevant Islamic Religious Education policies